Suomi, kulttuurihistoria ja kulttuurisuuden haaste - Salmi Hannu (Finland, 2025)
It is often argued that Finnish historians were the first ones in Scandinavia to publish a comprehensive cultural history of their country. The four-volume Suomen kulttuurihistoria (Cultural History of Finland) was published in 1933–1936. By now, several cultural histories have been produced. “Finland” has been the focus and the defining concept of these works, in which culture has been seen on the one hand as a whole, as an entity that has its boundaries, on the other hand as a web of significance that conveys itself through perspectives into the past. This essay concentrates on the ontological premises of cultural history and discusses both the notion of ‘culture’ and the idea of ‘culturality’. It is essential to further examine the current criticism towards the anthropocentrism of historical and cultural studies. In the study of the construction of ‘Finland’, the idea of culturality can be expanded by paying more attention to the interplay between human and non-human factors.